The Effects Of Teacher ICT Skills, Beliefs And Training On ICT Integration Among Teachers In Malaysian Schools - Jamiat, Nurullizam (2012)
The processes of integrating information and communication technology (ICT) into teaching and learning are complex, but most studies conducted in the Malaysian context only involved simplistic causal descriptions that applied bivariate analyses where many active variables were ignored or assumed to have been held constant. This study applied the Structural Equation Modeling method of data analysis to examine the direct and indirect effects of ICT skills, beliefs, and training factors on ICT integration into teaching, learning and everyday work among teachers. A hypothesized model representing the factors and relationships between the factors towards ICT integration was derived from the diffusion of innovation theory, technology acceptance model, and literature review. The questionnaire for this study was adapted from the ICT integration survey developed by the Scottish Executive Education Department. A total of 7,320 questionnaires were sent to teachers of all specializations nationwide. 1,668 questionnaires were returned and 1,318 responses were usable for data analysis after the screening process.